2016
DOI: 10.1186/s13256-016-0966-8
|View full text |Cite
|
Sign up to set email alerts
|

Physiological adaptation after a 12-week physical activity program for patients with Prader–Willi syndrome: two case reports

Abstract: BackgroundPhysical activity programs are a powerful tool against several diseases including obesity and their comorbidities. Prader–Willi syndrome is the most common genetic disease associated with obesity, and brings with it behavioral and emotional problems that need complex management. Research into the effect of physical activity programs on Prader–Willi syndrome is limited and it is frequently argued that if a physical activity program is too complex, the participants are more likely to drop out. Therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Our training program was not long term and was of a lower intensity than previous study programs. 13 15 , 18 , 40 To accommodate the PWS Association timetable, we provided one 2-hour treatment per week for 12 weeks, which might have been insufficient to achieve significant hand muscle strength and dexterity improvements. Future studies should consider the use of higher intensity and higher frequency muscle strength training, such as once per day for 12 weeks, or the addition of simple, effective, and feasible home-based training programs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our training program was not long term and was of a lower intensity than previous study programs. 13 15 , 18 , 40 To accommodate the PWS Association timetable, we provided one 2-hour treatment per week for 12 weeks, which might have been insufficient to achieve significant hand muscle strength and dexterity improvements. Future studies should consider the use of higher intensity and higher frequency muscle strength training, such as once per day for 12 weeks, or the addition of simple, effective, and feasible home-based training programs.…”
Section: Discussionmentioning
confidence: 99%
“…Following previous studies 14 , 15 and in line with the timetable of the PWS Association, a 12-week training program was conducted with a small group of six participants. To ensure compliance and safety, participants were supervised and guided by three trained and certified occupational therapists.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participation in exercise sessions was excellent, as well as the satisfaction from both participants and their families. Studies that implemented home‐based exercise training programmes, either supervised or non‐supervised, usually reported high participation in exercise sessions compared to programmes based outside the home (Amaro et al, ; Capodaglio et al, ; Rubin, Wilson, Dumont‐Driscoll, et al, ). Instructors involved in this programme reported they had to adapt to the participants’ psychological and cognitive disorders and physical limitations associated with PWS, and sometimes to patients’ fatigue and lack of motivation.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the specific impairment of executive functions and psychopathological features in this syndrome, integration of an exercise programme as part of daily routine along with individual interaction with health professionals might be especially important (Chevalere et al, ). Two case reports suggested that a home‐based exercise training programme supervised by a PA instructor was feasible and well‐accepted by children with PWS, although mixed findings were reported on changes in body mass and body composition, habitual PA and physical fitness (Amaro et al, ). A recent controlled study conducted in youth with PWS reported that a home‐based exercise training programme facilitated by parents improved muscle strength and gross motor skill proficiency and decreased body mass in subjects who experienced an increase in objectively measured MVPA (Rubin, Wilson, Castner, & Dumont‐Driscoll, ; Rubin, Wilson, Dumont‐Driscoll, et al, ).…”
Section: Introductionmentioning
confidence: 99%